The Reserve Currency Role of the Dollar: Blessings or Burden to the United States? - Salant, Willliam A. (The Review of Economics and Statistics, 1964)
SINCE Professor Triffin launched his plan five years ago, the international liquidity problem has been the subject of vigorous discussion. The debate will probably reach a climax this year and next when the IMF and the Group of Ten complete their studies of the subject. Some proposals for international monetary reform would retain the role of the dollar as the principal reserve currency, perhaps strengthening it by further building up what Under Secretary Roosa has called its perimeter defenses. Others envisage that the dollar would share that role with other currencies, as in the Posthuma and Lutz plans, or with a new international unit which would represent a claim against the International Monetary Fund, as in the proposals advanced by Chancellor of the Exchequer Alaudling in 1962 and by E. M. Bernstein in 1963. Finally, Triffin's original plan would transfer the reserve currency function outright from national currencies to an international unit.' Miost of the discussion has centered around the relative merits of the different plans in providing adequate, effective, and stable arrangements for supplying international reserves and settling international balances and rightly so, since this is clearly the crucial issue. A subsidiary question, which has recently received some attention in the United States and has been discussed for some time in the United Kingdom, is whether a country gains or loses by having its currency used as an international reserve by other countries. This question is closely related to the central issue, and is also of particular interest to the reserve currency countries. It is the subject of the present paper. Space limitations make it necessary to confine the discussion to one aspect of the question.2